Fragmented or included? – Impacts of globalization on Addis Ababa’s poor - Tröger, Sabine (ERDKUNDE, 2009)
The article challenges the thesis of ‘fragmentation’ in its radical connotation of a final and irrevocable exclusion from globalizing worlds in current theory discourses, an exclusion of those not expressively needed by globalization. The example of 350 households in Addis Ababa, who were forcibly evicted from their inner-city homesteads in the course of processes of globalization and privatization, depicts a more differentiated societal development. These actors, the victims of the forced eviction, are able to realize a chance of re-inclusion, which, ironically, occurs through the very same globalization processes, which had evicted them beforehand. Against the background of this empirical evidence, the thesis of ‘fragmentation’ in the sense of an irrevocable and final exclusion as the systemic ultimate implication of globalization is rejected.